Cenários de mudança global, cenários de desigualdade local: as territorialidades camponesas em Patzicía, CH, Guatemala - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This dissertation presents and analyzes the territorial transformations that took place in peasant communities in the municipality of Patzicía, from the changes introduced in rural areas through the neoliberal political-economic project led by the Guatemalan State. These transformations have been particularly striking in Patzicía since the 1970s, when a process of monopolization of the territory by capital was introduced, which sought to take advantage of the efficiency of the peasant unit and link these small producers to the world market for vegetables and fruits. The objective of the State, the oligarchy and the agro-producing bourgeoisie, was to modernize the agricultural production matrix without modifying the national agrarian structure. In this context, in Patzicía highly individualized kulak type farmers emerge and develop, who come into conflict with local peasants in the dispute for land, resources and consumption of work force, which ends up aggravating local inequality. In order to understand peasant communities, as well as their development and permanence in this context, we start from the concepts of work land versus business land, which ultimately explain the disputes over land in the countryside. To give a overview of this dispute, this dissertation presents the empirical case and the primary and secondary data of the long dialectical process of theft and constant recovery of peasant lands, from colonial times to the current disputes between peasants and kulaks in the municipality. But we explain it from the national context, understanding that the State has played an important role in this process, in which peasant communities constantly seek access to sufficient and quality land, to reaffirm or build their autonomy, their ecological logic and their political project, and in the specific case of Patzicía, linked to ancestral conceptions of land and territory. This study seeks to understand how the expansion and development of neoliberal capitalism in Guatemala, modifies and/or affects the processes of territorialization and the peasant way of life, based on the paradigmatic empirical case presented in the municipality. The study seeks, on the other hand, to discuss and analyze the peasant possibilities forms of territorialization, demonstrate the economic, political and ecological potential of peasant units in the dynamization of society-nature relations, and as an alternative to the negative social and ecological effects that capitalism neoliberal brings. Finally, based on the studied processes, it is shown that only the real and immediate democratization of access to land, and all the natural resources that this means, can contribute to a substantial improvement in the living conditions of rural and peasant families, and in the sustainable application in agriculture of the innovative technical processes present in the 21st century.

Esta disertación presenta y analiza las transformaciones territoriales dadas en las comunidades campesinas del municipio de Patzicía, a partir de los cambios introducidos en el campo por el proyecto político-económico neoliberal del Estado guatemalteco. Estas transformaciones han sido particularmente llamativas en el municipio de Patzicía desde la década de 1970, cuando se introdujo un proceso de monopolización del territorio por el capital, que buscaba aprovechar la eficiencia de la unidad campesina y vincular a estos pequeños productores al mercado mundial de hortalizas y frutas. El objetivo era modernizar la matriz productiva agrícola sin modificar la estructura agraria nacional. En este contexto, en Patzicía surgen y se desarrollan agricultores tipo kulak, altamente individualizados, que entran en conflicto con los campesinos locales en la disputa por la tierra, los recursos y el consumo de mano de obra, lo que termina agravando la desigualdad local. Para entender las comunidades campesinas, así como su desarrollo y permanencia en este contexto, partimos de los conceptos de tierra de trabajo versus tierra de negocios, que explican en última instancia las disputas por la tierra en el campo. Para dar un panorama de esta disputa, esta disertación presenta el caso empírico y los datos primarios y secundarios del largo proceso dialéctico de robo y recuperación constante de tierras campesinas, desde la época colonial hasta las actuales disputas entre campesinos y kulaks en el municipio. Pero explicado desde el contexto nacional, entendiendo que el Estado ha jugado un papel importante en este proceso, en el que las comunidades campesinas buscan constantemente el acceso a tierras suficientes y de calidad, para reafirmar o construir su autonomía, su lógica ecológica y su proyecto político, en el caso específico de Patzicía, vinculado a concepciones ancestrales de tierra y territorio. Este estudio busca comprender cómo la expansión y desarrollo del capitalismo neoliberal en Guatemala modifica y/o afecta los procesos de territorialización y la forma de vida campesina, a partir del caso empírico presentado en el municipio. El estudio busca, por otro lado, discutir y analizar las diversas posibilidades de territorialización campesina, demostrar el potencial económico, político y ecológico de las unidades campesinas en la dinamización de las relaciones sociedad-naturaleza, y como alternativa a los efectos sociales y ecológicos del capitalismo neoliberal. Finalmente, con base en los procesos estudiados, se muestra que solo la democratización real e inmediata del acceso a la tierra, y todos los recursos naturales que esto significa, pueden contribuir a una mejora sustancial de las condiciones de vida de las familias rurales y campesinas, y en la aplicación sostenible en la agricultura de los procesos técnicos innovadores presentes en el siglo XXI.
Scenarios of global change, scenarios of local inequality: peasantry territorialities in Patzicía, CH, Guatemala
Keywords: Camponeses - Agricultura; CIENCIAS HUMANAS: GEOGRAFIA; Território; Territory; Campesinado; Campesinato; Capitalismo; Agricultura; Guatemala; Peasantry; Capitalism; Agriculture